The 7 habits of highly effective people - Covey, Stephen R. (London : Simon & Schuster, 2020)
The 7 Habits of Highly Effective People is a self-help and personal development book that provides a principle-centered approach to success. Stephen R. Covey presents seven habits that help individuals become more effective in their personal and professional lives.
Keywords: Psychology-Self help